2022
DOI: 10.1186/s12891-022-05326-5
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes after degenerative lumbar spine surgery in rheumatoid arthritis patients -a propensity score-matched analysis

Abstract: Background Although treatment options for rheumatoid arthritis (RA) have evolved significantly since the introduction of biologic agents, degenerative lumbar disease in RA patients remains a major challenge. Well-controlled comparisons between RA patients and their non-RA counterparts have not yet been reported. The objective of the present study was to compare postoperative outcomes of lumbar spine surgery between RA and non-RA patients by a retrospective propensity score-matched analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Significant increases in the risks of sepsis, urinary tract infection, deep vein thrombosis, 90-day emergency room visits, and 90-day readmissions were found in MS patients who had undergone primary posterior lumbar fusion compared with lower risks in patients without MS [ 22 ]. Another study compared postoperative outcomes of lumbar spine surgery between RA and non-RA patients through retrospective propensity score-matched analysis, finding that RA had poorer postoperative outcomes for LDD surgery compared with P S-matched non-RA patients [ 23 ]. Similarly, the present study demonstrated an association between pre-existing PsA and poorer postoperative complications after LDD surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in the risks of sepsis, urinary tract infection, deep vein thrombosis, 90-day emergency room visits, and 90-day readmissions were found in MS patients who had undergone primary posterior lumbar fusion compared with lower risks in patients without MS [ 22 ]. Another study compared postoperative outcomes of lumbar spine surgery between RA and non-RA patients through retrospective propensity score-matched analysis, finding that RA had poorer postoperative outcomes for LDD surgery compared with P S-matched non-RA patients [ 23 ]. Similarly, the present study demonstrated an association between pre-existing PsA and poorer postoperative complications after LDD surgery.…”
Section: Discussionmentioning
confidence: 99%